Combined U-Pb SHRIMP and Hf isotope study of the Late Paleozoic Yaminué Complex, Rio Negro Province, Argentina: Implications for the origin and evolution of the Patagonia composite terrane - Chernicoff, Carlos; Zappettini, Eduardo; Santos, Joao; McNaughton, Neal; Belousova, E (Elsevier, 2013)
We have carried out zircon U-Pb SHRIMP dating and Hf isotope determinations on a biotite paraschist and on a tonalitic orthogneiss of the Yaminué Complex, and re-evaluate this complex in the broader context of the tectonic evolution of the Patagonia composite terrane. In the metasedimentary unit (msuYC), the youngest detrital zircon dated at 318 ± 5 Ma (Mississippian/Pennsylvanian boundary) indicates a Pennsylvanian (or younger) depositional age. The three main age populations peak at 474, 454 and 374 Ma. Preliminary Hf isotope data for two detrital zircons (447 and 655 Ma) yielded ε(Hf) values of −0.32 and 0.48, indicating that their primary sources contained small amounts of recycled crustal components (of Calymmian age; TDM 1.56 Ga). Zircons from the orthogneiss (miuYC; intrusive into msuYC) show a crystallization age of 261.3 ± 2.7 Ma (Capitanian; late middle Permian) which is broadly coeval with deformation, and Neoarchean–Paleoproterozoic inheritance. Meaningful core-rim relationship between Neoarchean zircon cores and late Permian rims is well defined, indicating the occurrence of Archean crust in this sector of Patagonia. Hf TDM of Permian zircons is mainly Meso-Paleoarchean (2.97–3.35 Ga), with highly negative ε(Hf) values (ca. −33). Hf TDM of inherited Neoarchean zircon cores is also Meso-Paleoarchean (3.14–3.45 Ga) but more juvenile (ε(Hf) = −0.3). Hf isotopes reinforce the presence of unexposed ancient crust in this area.Combining geological and isotope data, as well as geophysical models, we identify the Yaminué Complex within the La Esperanza-Yaminué crustal block flanked by two other, distinct crustal blocks: the Eastern block which forms part of the Patagonia terrane sensu stricto, located in the eastern Patagonian region, and the Western block forming part of the Southern Patagonia terrane. Their origins and timing of amalgamation to form the Patagonia composite terrane are also discussed.